Gender Ethics in Islamic Economic Thought and Its Influence on Ethical Financial Behaviour - Anshori, Afif; Setiawati, Rini (Inovasi Analisis Data, 2025)
Objective: This study examines how Islamic ethical cognition influences ethical financial behaviour. Islamic ethical cognition comprises an understanding of Maqasid al-Shariah. It also comprises internalization of ethical principles and gender perspective.Methods: A quantitative approach was employed, with data analysed using EViews. A structured questionnaire was used to measure the key constructs.Results: The results of the study indicate that ethical financial behaviour can be predicted by the three aspects of Islamic ethical thinking, with the best results achieved when ethical principles are fully accepted. The relationship between understanding Maqasid al-Shariah and ethical practices, as well as between the internalization of principles and ethical behavior, is greatly influenced by religious dedication. However, the study's findings show that there is no statistically significant relationship between gender, ethical perspective, and financial behavior. These results demonstrate the importance of being a good person (akhlaq) in Islamic banking and finance, as well as the potential of religion to encourage better behavior.Novelty: We introduce an integrated model that synthesizes the teleological framework of Maqasid al-Shariah with Islamic virtue ethics and contemporary ethical decision-making theory. It looks at how religious belief affects the way Islamic ethical philosophy is put into financial practice, offering a new way of thinking about the cognitive-behavioral pathway in Islamic finance. Research Implication: This study provides a solid theoretical framework by integrating classical Islamic philosophy with modern behavioral science. It is recommended that Islamic financial institutions develop comprehensive educational programs that integrate intellectual, character, and spiritual development to foster authentic ethical behaviour in financial practices.